Número cromosómico y apareamiento meiótico en Turbinicarpus valdezianus (Möller) Glass & Foster (Cactaceae) - Reyes-Valdés, M. Humberto; Gómez-Martínez, Martha; García-Osuna, Hermila Trinidad (Instituto de Ecología, A.C., 2000)
In this research the chromosomes of Turbinicarpus valdezianus were studied in diakinesis and metaphase I, from native plants located near Saltillo, Coahuila (Mexico). A chromosome number 2n = 2x = 22 was found, which is consistent with the basic number x = 11, previously reported for other members of the cactus family. The normal bivalent pairing observed in all the analyzed cells indicates that this is a diploid species with regular chromosome segregation. The analysis of meiotic configuration frequencies supports the hypothesis of one or more chromosome pairs being non-metacentric.